2019
DOI: 10.5601/jelem.2018.23.4.1724
|View full text |Cite
|
Sign up to set email alerts
|

Visible and near-infrared hyperspectral imaging to describe properties of conventionally and organically grown carrots

Abstract: This paper discusses the potential of visible and near-infrared hyperspectral imaging to describe properties of conventionally and organically grown carrots. 140 samples of four Lithuanian carrot cultivars were scanned using a VNIR400H hyperspectral camera, capable of covering the spectral range of 400-1000 nm with a sampling interval of 0.6 nm. Half of the samples were grown under organic farming conditions and the remainder under conventional conditions. Chemical and electro-chemical properties, i.e. nitrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Cultivars developed in Lithuania are better adapted to the local meteorological and soil conditions, and are distinguished by rich biochemical composition and taste properties. Cultivars are productive and resistant to diseases and also have an excellent market appearance [ 1 , 2 , 3 , 4 , 5 ]. When breeding vegetables, it takes on average 10–12 years to develop a new cultivar or a hybrid.…”
Section: Introductionmentioning
confidence: 99%
“…Cultivars developed in Lithuania are better adapted to the local meteorological and soil conditions, and are distinguished by rich biochemical composition and taste properties. Cultivars are productive and resistant to diseases and also have an excellent market appearance [ 1 , 2 , 3 , 4 , 5 ]. When breeding vegetables, it takes on average 10–12 years to develop a new cultivar or a hybrid.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike broadband satellite data, hyperspectral data has numerous contiguous spectral channels with a potential ability to detect and characterize subtle differences in plant traits such as those induced by different fertilizer application regimes in relation. For example,Česonienė, et al [17] demonstrated that hyperspectral data could discriminate between conventionally and organically grown carrots in Lithuania to Jeffries-Matusita distances ranging between 1.98 and 2.00. They attributed their results to the ability of hyperspectral data to discern on the variations in the cell structure conditions and canopy structure of the carrots grown under different farming methods.…”
Section: Introductionmentioning
confidence: 99%